TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Luis Pertierra; Gilda Varliero; Andrés Barbosa; Elisabeth Biersma; Peter Convey; Steven Chown; Don Cowan; Asunción De Los Rios; Pablo Escribano-Alvarez; Diego Fontaneto; Ceridwen Fraser; Mathew Harris; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.